2014
DOI: 10.1128/iai.01973-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocyte Subsets at Homeostasis and Their Perturbation in Numbers and Function in Filarial Infection

Abstract: To characterize the function and plasticity of the major human circulating monocyte populations and to explore their role in systemic helminth infection, highly purified (by flow-based sorting) human monocyte subsets [nonclassical]) were examined at homeostasis and after activation. Among these three subsets the classical and intermediate subsets were found to be the major sources of inflammatory and regulatory cytokines, as well as cytokines/chemokines associated with alternative activation, whereas the nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Non-classical monocytes did not show a detectable response to IL-4. This result is consistent with other studies, which found that non-classical monocytes have a reduced cytokine response to IL-4 [ 23 ]. Differences between CD16+ and CD16- monocytes in induction of some cell markers during dendritic cell differentiation by GM-CSF, IL-4 and TNFα have also been reported [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Non-classical monocytes did not show a detectable response to IL-4. This result is consistent with other studies, which found that non-classical monocytes have a reduced cytokine response to IL-4 [ 23 ]. Differences between CD16+ and CD16- monocytes in induction of some cell markers during dendritic cell differentiation by GM-CSF, IL-4 and TNFα have also been reported [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…Higher levels of binding of the 14–23 antibody were observed on classical monocytes, raising the possibility that other peptides in addition to CLIP may generate the conformation recognized by mAb 14–23, although this antibody was generated by immunization of HLA-DR3 transgenic mice with HLA-DR3/CLIP complexes [ 17 ]. Interestingly, the classical monocyte has been observed to be the most efficient at inducing autologous T cell proliferation, although by a small degree [ 21 , 23 ]. These results suggest that although the intermediate subset has the highest level of MHCII, the lowest CLIP:MHCII ratio, and high levels of costimulatory molecules [ 7 ], the classical subset may present relevant self-peptides for homeostatic proliferation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of function and plasticity of monocytes have been described in parasitic infections [4850] and clearly demonstrated the differential polarization of these cells as described for macrophages. In our study, phenotypic and molecular parameters were evaluated in circulating monocytes from hookworm-infected individuals to investigate the profile of activation and polarization of these cells.…”
Section: Discussionmentioning
confidence: 79%
“…It is worth mentioning that the increase in the percentage of monocytes expressing CD16 was also observed in other pathological conditions, e.g. during bacterial, viral or parasitic infections [20] and in acute or chronic conditions such as sepsis or atherosclerosis [8], chronic liver disease [21], rheumatoid arthritis [22], and renal diseases [23,24].…”
Section: Discussionmentioning
confidence: 83%